IMPLEMENTASI SISTEM BOARDING SCHOOL SEBAGAI UPAYA PEMBENTUKAN KARAKTER ISLAMI DI SMK ANDALUSIA 1 WONOSOBO - Fatimah, Fatimah; Majid, Abdul; Imron, Ali (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2020)
The aims of this study are knowing how to build Islamic character in SMK Andalusia 1 Wonosobo and knowin what are the supporting and inhibiting factors in the process of implementing the boarding school system as an effort to build the Islamic character of SMK Andalusia 1 Wonosobo. The research method that used in this study is a qualitative research. The data related to this study were collected through direct interviews with the relevant informants, observations made in the boarding school and school environment by participating in activities and personal observations and documentation. The results of this study showed obtained are the implementation of the boarding school system as an effort to form Islamic character in students at SMK Andalusia 1 Wonosobo first through habits of daily activities that have been determined, such as congregational prayers, book studies, and weekly activities such as khitobah and ro'an. Congregational prayer activities aim to shape the religious character of children, while book studies aim to deepen knowledge and knowledge about religion. While weekly activities such as khitobah and ro'an train self-confidence and awareness in maintaining cleanliness. However, it is undeniable that the tight schedule of activities on board has become a complaint for students.